The Relationship between Personal Hygiene and the Incidence of Diarrhea - Aminah, Siti; Wahyudi, Wahyudi; Siregar, Putra Apriadi (Indonesian Journal of Global Health Research, 2024)
Diarrhea is a microorganism infectious disease characterized by defecation with a liquid consistency and frequency more than three times a day. The purpose of this study was to analyze the relationship between personal hygiene and the incidence of diarrhea in public elementary schools 016747 Range. This study used quantitative methods with a cross sectional approach accompanied by data collection using questionnaires. The statistical test used in this study used univariate &; bivariate test analysis to determine the relationship between personal hygiene attitude behavior towards diarrhea. The incidence of diarrhea in elementary schools 016747 in 2024 shows that some respondents who suffer from diarrhea, namely 41 people (58%) and 29 people (41%) do not experience diarrhea. The results of this study show that diarrhea occurs in personal hygiene behavior related to defecation behavior, hand washing behavior and nail hygiene behavior.